Analysis of Technical and Operational Aspects of Business Feasibility (Case Study of Purse Seine Fisheries at TPI Brondong Port, Lamongan) - Devah Sukmawati; Abdur Rohman (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
There are two ways of handling fishing catches of purse seiner in TPI Pelabuhan Brondong Lamongan, using freezer or using ice and salt, that caused the difference of the price, so that means that the feasibility level of freezer purse seiner and salt purse seiner were different. The purpose of this research was to analyze the technical aspects of purse seiner (construction, operating techniques, areas and operating seasons, the size of the vessel and the machines) and the feasibility of freezer purse seiner and salt purse seiner in TPI Pelabuhan Brondong Lamongan. This research used descriptive method, sampling with purposive sampling. Data analysis were consisted of analysis of the technical aspects, statistic analysis (normality test and t test) and financial analysis.The results of the technical aspects purse seiner were consisted of float line, sinker line, head rope, purse line, selvedge, body nets, bunt, float, sinker, rings, operation phase included the preparation, fishing ground, setting and hauling, the operation areas of purse seiner are in Java Sea, Sulawesi waters, Borneo waters and Natuna Sea, the peak seasons are on August - December, the size of purse seine vessel were between 50 - 90 GT. Normality test showed that data distribution were normal. t-test showed that value of production and the production of freezer and ice and salt were different. The results of the financial analysis showed that freezer purse seiner and ice and salt purse seiner fishing business were feasible. Freezer purse seiner was more feasible than ice and salt purse seiner.